2009
DOI: 10.1002/pbc.21925
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of high‐dose methotrexate in infants treated for acute lymphoblastic leukemia

Abstract: Our data provide no support for a change in the dosing rules for MTX used in Interfant-99. However, in view of the poor treatment results for infants, one might consider increase in the dose for patients who reach plasma levels below median after the first MTX dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In the clinic, plasma concentration of MTX and release of calcium folinate are monitored dynamically to reduce the occurrence of chemotherapy-induced adverse effects. A previous study demonstrated the existence of individual differences in the pharmacokinetics, effectiveness, and toxicity of MTX, suggesting there might be some potential gene targets affecting the pharmacokinetics and pharmacodynamics of MTX [12]. FPGS is an important enzyme in MTX metabolism, and catalyzed poly glutamic acid is the core of folate antagonists-associated cytotoxic therapy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, plasma concentration of MTX and release of calcium folinate are monitored dynamically to reduce the occurrence of chemotherapy-induced adverse effects. A previous study demonstrated the existence of individual differences in the pharmacokinetics, effectiveness, and toxicity of MTX, suggesting there might be some potential gene targets affecting the pharmacokinetics and pharmacodynamics of MTX [12]. FPGS is an important enzyme in MTX metabolism, and catalyzed poly glutamic acid is the core of folate antagonists-associated cytotoxic therapy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 population pharmacokinetic study including infants <6 months has been published, but it was in patients with acute lymphoblastic leukaemia, had a small patient population of infants only ( n = 17), and had limited covariates (weight, age, body surface area and sex) . Other pharmacokinetic studies in infants have been published but often with contradictory pharmacokinetic results . These limited evaluations have been inadequate, suffering from small numbers of infants, and heterogeneous enrolment criteria and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…11 Other pharmacokinetic studies in infants have been published but often with contradictory pharmacokinetic results. 12,13 These limited evaluations have been inadequate, suffering from small numbers of infants, and heterogeneous enrolment criteria and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…PK analysis of highdose MTX (5 g/m 2 /dose) in the Interfant-99, applying the aforementioned dose reduction rule, indicated a slightly lower MTX clearance in younger infants, but the toxicity profile was similar to that for older infants. 37 …”
Section: Chemotherapymentioning
confidence: 99%